ISAKOS upper extremity committee consensus statement on the need for diversification of the Rockwood classification for acromioclavicular joint injuries - Beitzel, Knut; Mazzocca, Augustus D; Bak, Klaus; Itoi, Eiji; Kibler, William B; Mirzayan, Raffy; Imhoff, Andreas B; Calvo, Emilio; Arce, Guillermo; Shea, Kevin (Arthroscopy, 2014)
Optimal treatment for the unstable acromioclavicular (AC) joint remains a highly debated topic in the field of orthopaedic medicine. In particular, no consensus exists regarding treatment of grade III injuries, which are classified according to the Rockwood classification by disruption of both the coracoclavicular and AC ligaments. The ISAKOS Upper Extremity Committee has provided a more specific classification of shoulder pathologies to enhance the knowledge on and clinical approach to these injuries. We suggest the addition of grade IIIA and grade IIIB injuries to a modified Rockwood classification. Grade IIIA injuries would be defined by a stable AC joint without overriding of the clavicle on the cross-body adduction view and without significant scapular dysfunction. The unstable grade IIIB injury would be further defined by therapy-resistant scapular dysfunction and an overriding clavicle on the cross-body adduction view.